Decomposition method for nonlinear isothermal magnetostatic atmospheres - İnç, Mustafa; Evans, DJ (Taylor & Francis Ltd, 2005)
In this article, the equations of magnetohydrodynamic (MHD) equilibria for a plasma in a gravitational field are solved by using the Adomian decomposition method (ADM). Using this approach, we obtained the numerical solutions of this type of equations. Numerical illustrations on well-known MHD equations with the exact solutions indicate that the decomposition method is efficient, reliable and accurate. Most of the symbolic and numerical computations have been performed using the Computer Algebra-System-Mathematica.
Keywords: ADM; Adomian polynomials; nonlinear elliptic BVPs; isothermal magnetostatic atmospheres